Availability of applying diaphragm matching with the breath-holding technique in stereotactic body radiation therapy for liver tumors. Issue 4 (April 2016) - Kawahara, Daisuke; Ozawa, Shuichi; Kimura, Tomoki; Nakashima, Takeo; Aita, Masamichi; Tsuda, Shintaro; Ochi, Yusuke; Okumura, Takuro; Masuda, Hirokazu; Ohno, Yoshimi; Murakami, Yuji; Nagata, Yasushi
Highlights: We investigated the feasibility of diaphragm matching for liver tumors. Diaphragm matching suppresses variations in respiratory tumor motion. Diaphragm matching was useful in all (C-C, A-P, L-R) direction. Although it was not showed in our previous study, PTV margin could be reduced. Graphical Abstract: Abstract: Purpose: Image-guided radiotherapy (IGRT) based on bone matching can produce large target-positioning errors because of expiration breath-hold reproducibility during stereotactic body radiation therapy (SBRT) for liver tumors. Therefore, the feasibility of diaphragm-based 3D image matching between planning computed tomography (CT) and pretreatment cone-beam CT was investigated. Methods: In 59 liver SBRT cases, Lipiodol uptake after transarterial chemoembolization was defined as a tumor marker. Further, the relative isocenter coordinate that was obtained by Lipiodol matching was defined as the reference coordinate. The distance between the relative isocenter coordinate and reference coordinate, which was obtained from diaphragm matching and bone matching techniques, was defined as the target positioning error. Furthermore, the target positioning error between liver matching and Lipiodol matching was evaluated. Results: The positioning errors in all directions by the diaphragm matching were significantly smaller than those obtained by using by the bone matching technique (p < 0.05). Further, the positioning errors in the A-P and C-C directions that were obtained by using liver matching were significantly smaller than those obtained by using bone matching (p < 0.05). The estimated PTV margins calculated by the formula proposed by van Herk for diaphragm matching, liver matching, and bone matching were 5.0 mm, 5.0 mm, and 11.6 mm in the C-C direction; 3.6 mm, 2.4 mm, and 6.9 mm in the A-P direction; and 2.6 mm, 4.1 mm, and 4.6 mm in the L-R direction, respectively. Conclusions: Diaphragm matching-based IGRT may be an alternative image matching technique for determining liver tumor positions in patients.